2016 IEEE 27th Annual International Symposium on Personal, Indoor, and Mobile Radio Communications (PIMRC) 2016
DOI: 10.1109/pimrc.2016.7794739
|View full text |Cite
|
Sign up to set email alerts
|

Hardware testbed for sidelink transmission of 5G waveforms without synchronization

Abstract: This paper details a hardware testbed conceived for studying the impact of the lack of synchronism between transmitters on several 5G waveform candidates, which is of special relevance for car-to-car communications. The experimental results show that a proper fitting of waveforms in a software-defined platform would permit increasing the range of communication between cars without peer-to-peer synchronization, paving the way for the real development of collision avoidance messages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The authors have characterized different waveform candidates based on their resulting BER and Adjacent Channel Power Ratio (ACPR) taking into account power amplifier nonlinearities. A hardware testbed has been presented in [3] which has been used to conduct asynchronous multiple access experiments using multiple transmitters. It has been shown that OFDM is less robust under lack of synchronization, and waveform candidates such as UFMC and FBMC have shown improved performance in terms of BER.…”
Section: Related Workmentioning
confidence: 99%
“…The authors have characterized different waveform candidates based on their resulting BER and Adjacent Channel Power Ratio (ACPR) taking into account power amplifier nonlinearities. A hardware testbed has been presented in [3] which has been used to conduct asynchronous multiple access experiments using multiple transmitters. It has been shown that OFDM is less robust under lack of synchronization, and waveform candidates such as UFMC and FBMC have shown improved performance in terms of BER.…”
Section: Related Workmentioning
confidence: 99%
“…OFDM implementations in 4G technologies are sensible to the lack of synchronization between V2V emitters [9]. However, there exist mechanisms that improve OFDM robustness (e.g.…”
Section: Use Of New Waveformsmentioning
confidence: 99%
“…So far, many experimental testbeds including multiple waveforms have been developed [11][12][13][14][15][16]. However, they mainly focus on dedicated implementations for isolated waveforms, without considering a versatile implementation able to generate different waveforms according to a harmonized framework with hardware reuse.…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%